The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.renene.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of energy and exergy analysis of fossil plant, ground and air source heat pump building heating system

Abstract: The energy and exergy flow for a space heating systems of a typical residential building of natural ventilation system with different heat generation plants have been modeled and compared. The aim of this comparison is to demonstrate which system leads to an efficient conversion and supply of energy/exergy within a building system. The analysis of a fossil plant heating system has been done with a typical building simulation software IDA-ICE. A zone model of a building with natural ventilation is considered an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 4 publications
1
33
1
1
Order By: Relevance
“…Zhou and Gong [13] studied the whole chain of exergy flows for a building heating and cooling system by hourly varying the reference state. Balta et al [14], Lohani [15], and Lohani and Schmidt [16] studied different heat sources for building heating applications. Zmeureanu and Wu [17] studied the energy and exergy performance of residential heating systems.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou and Gong [13] studied the whole chain of exergy flows for a building heating and cooling system by hourly varying the reference state. Balta et al [14], Lohani [15], and Lohani and Schmidt [16] studied different heat sources for building heating applications. Zmeureanu and Wu [17] studied the energy and exergy performance of residential heating systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Self et al [5] compared GHP heating with other heating options, and found out that the use of GHP systems is economically advantageous if the local electricity price is low, which also has the lowest effect on the environment considering the low CO 2 emissions. An energy and exergy flow analysis was performed by Lohani and Schmidt [6] in 2010 considering different heating options, including fossil fuels, ground and air source heat pump systems. The result of this comparison revealed that the GHP heating system is better than air source heat pumps and other conventional heat options.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on vertical closed systems focused mainly on (a) the comparison between these systems and other heat pump technologies such as air source heat pumps (e.g., Lohani and Schmit 2010;Urchueguía et al 2008;Petit and Meyer 1998;Said et al 2010;Liu and Hong 2010); (b) the energy, environmental, and techno-economic aspects of the conventional heating and cooling systems' substitution (e.g., Huchtemann and Müller 2012;Pardo and Thiel 2012;Boait et al 2011;Shonder and Hughes 2006;Rodríguez et al 2012); (c) the strategic design, controlling procedure, and the benefits of combined (e.g., Chen and Yang 2012;Xi et al 2011;Wang et al 2010;Pärisch et al 2014;Rad et al 2013) or hybrid systems (e.g., Pardo et al 2010;Man et al 2010;Yi et al 2008;Yu et al 2014;Alavy et al 2013), systems which combine GCHP and other RES (e.g., solar panels, PV panels) or conventional (e.g., oil-fired boiler) technology; and (d) the overall design procedure of vertical GCHP systems in order to improve the efficiency and minimize the installation and operation costs taking into account the GHEx configuration, the geophysical properties of the materials and soil, as well as the climate conditions of the installing area (e.g., Robert and Gosselin 2014;Alalaimi et al 2013;Chung and Choi 2012;Zanchini et al 2010;Sanaye and Niroomand 2009;Luo et al 2013). Urchueguía et al (2008), for example, compared a vertical GCHP system and an air to water heat pump system for heating and cooling in typical conditions of the European Mediterranean coast.…”
Section: Introductionmentioning
confidence: 99%